Diagnostic performance of computed tomography digital subtraction angiography of the lower extremities during haemodialysis in patients with suspected peripheral artery disease. Issue 3 (August 2021) - Masuda, T.; Funama, Y.; Nakaura, T.; Sato, T.; Okimoto, T.; Masuda, S.; Yamashita, Y.; Yoshiura, T.; Noda, N.; Baba, Y.; Awai, K.
Abstract: Introduction: With intra-arterial digital subtraction angiography (DSA) considered as the gold standard, we compared the diagnostic value of computed tomography angiography (CTA) and computed tomography-digital subtraction angiography (CT-DSA in hemodialysis (HD) patients suspected of having lower limb peripheral artery disease (PAD). Methods: In this retrospective study, we enrolled 220 HD patients with suspected PAD. CT-DSA images were obtained by subtracting unenhanced images from enhanced images. The research team calculated the area under the curve (AUC), sensitivity, specificity, positive and negative predictive value (PPV, NPV), and recorded the diagnostic accuracy between the CTA and CT-DSA images using the DSA as gold standard. Visual evaluation of calcifications in the peripheral arteries were also compared between CTA and CT-DSA images. Results: At the above-knee level, the CTA AUC [95% confidence interval (CI)] was 0.68 (CI 0.64–0.72), sensitivity and specificity were 60 and 81%, PPV and NPV were 85 and 53%, and accuracy was 67%. Below the knee, these values were 0.66 (CI 0.62–0.70), 71 and 79%, 79 and 47%, and 66%. For CT-DSA, above-knee, the AUC [95% CI] was 0.88 (CI 0.85–0.91), sensitivity and specificity were 84 and 92%, PPV and NPV were 89 and 97%, and accuracy was 93%. Below the knee, these values were 0.95 (CI 0.93–0.97), 95 and 93%, 96 and 83%, and 93%. The scores for the visualization of calcification in the peripheral arteries was significantly higher for CT-DSA than CTA (p < 0.05). Conclusions: CT-DSA helps to assess stenotic PAD with high calcification in the lower extremities of HD patients. Implications for practice: On CT-DSA images, the severity of vascular calcification can be assessed for HD patients suspected of PAD of the lower extremities.